THE REALITY OF SOME SPECIALIZED TASKS OF HUMAN RESOURCES MANAGEMENT IN AGRICULTURAL EXTENSION SYSTEM IN MIDDLE REGION PROVINCES OF IRAQ - & Ridh, Jihad (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
The research aimed to explore the reality of some specialized tasks of human resources management in agricultural extension and to reach the research aim, a questionnaire form was prepared according to specialists' opinions and their agreements. The scale questionnaire of the reality of some specialized tasks of human resources management included 103 items distributed on 7 axis: planning for human resources, occupational description, incentive system, workers training and developinge, valuation of workers performance, services provided to workers, and  work relations among the workers,The research was conducted on a random sample of 50% of Iraqi middle provinces (Baghdad, Karblaa, Najaf, Wasit). A random sample about 52% of the agricultural divisions of these provinces of 27 agricultural divisions were chosen, Limitedsearch(166) managers representing units Agricultural Extension device managers, as well as the directors of the departmentsof agricultureand agriculturalpeople andthe management of humanresources , Results showed that all specialized occupations or tasks of human resources management in agricultural extension system were applied, but in different degrees, The researcher recommended the necessity of adopting this research by agricultural extension system to improve the management of human resources.